Antibiotic utilization in Iran 2000-2016: Pattern analysis and benchmarking with organization for economic co-operation and development Countries - Hadi Abbasian; Mohammad Hajimolaali; Alireza Yektadoost; Saman Zartab (Wolters Kluwer Medknow Publications, 2019)
Objectives: Antibiotic resistance is the main threat to health all over the world. The consumption of antibiotics is one of the factors causing the emergence of multidrug resistance. The purpose of this study was to recognize the patterns, trends, and changes of consumption in Iran and to compare them with those of Organization for Economic Co-operation and Development (OECD) countries. Methods: The data were collected from a national pharmaceutical wholesale data bank. Defined daily dose (DDD) or DDDs per 1000 inhabitants per day (DID) was calculated as a standard indicator for the consumption over 17 years. Results: Were benchmarked with the consumption of OECD countries. Drug utilization 90% (DU90%) method was used to assess the drug consumption pattern. Findings: The antibiotic consumption jumped up from 33.6 DID to 60 DID from 2000 to 2016. Compared to the average consumption of OECD countries, Iran has consumed antibiotics almost triple times. There were 9-11 chemical substances in the DU90% list during these years. Changes in DU90% list occurred within antibiotics classes during the study period. Although the total consumption growth was equal to 79% during these years, consumption of some pharmacological subgroups such as sulfonamide and aminoglycosides has decreased. Conclusion: Albeit the existence of surveillance system for health-related infectious diseases, the consumption of antibiotics has increased drastically, which illustrates the necessity of comprehensive and effective national antibiotic stewardship.